Studi Sifat Mekanik Magnesium AZ31 Hasil Proses Pengecoran Tekan (Squeeze Casting) - Iqbal, Muhammad; Sukmana, Irza; Burhanuddin, Yanuar (Jurnal Energi Dan Manufaktur; Vol 11 No 1 (2018): Published in April 2018, 2018)
Magnesium forms 2% in the earth's crust, magnesium is widely used in industry.  For example, industrial machinery and electronics, and many developed in the field of biomedicine, especially in the field of orthopedics.  Magnesium about 60% is present in the human bones, therefore it has great potential for human body implants.  However, it is necessary to increase the mechanical and chemical properties of magnesium in order to be used for bone implant materials.  Production process using squeeze casting method.  Through this method, Liquid metal is given hydraulic pressure, so the mechanical properties of magnesium were better. In this research use temperature parameter = 450?C, pressure = 300 MPa, duration of press 1 minute and variation of holding time 7 and 9 minutes.  Magnesium AZ31 increased compared with samples without treatment.  Tensile strength with holding time 7 minutes equal to120.27 MPa, holding time 9 minutes was 128.77 MPa, and samples without treatment of was 94.63 MPa.  The magnesium hardness value of AZ31 decreased at 7 minute detention was 39 VHN, compared with the sample without treatment of was 41.8 VHN.  And the hardness value increased at holding time 9 minutes equal to 46.2 VHN.  However, it should be noted that excessive overheating and holding time may lead to decrease in magnesium mechanical properties of AZ31. Magnesium membentuk 2% pada kerak bumi, magnesium banyak digunakan pada industri.   Misalnya, industri mesin dan elektronik, dan banyak dikembangkan pada bidang biomedik, terutama di bidang orthopedi.  Magnesium sekitar 60% ada pada tulang manusia, oleh karna itu berpotensi besar untuk implan tubuh manusia. Namun, diperlukan peningkatan sifat mekanik dan kimia magnesium agar dapat digunakan untuk bahan implan tulang.  Proses produksi menggunakan metode pengecoran tekan. Melalui metode ini, logam cair diberi tekanan hidrolik, sehingga sifat mekanik magnesium lebih baik. Dalam penelitian ini menggunakan parameter temperatur = 450?C, tekanan = 300 MPa, durasi tekan 1 menit dan variasi holding time 7 dan 9 menit.  Magnesium AZ31 meningkat dibandingkan sampel tanpa perlakuan.  Kekuatan tarik dengan holding time 7 menit sebesar 120,27 MPa, holding time 9 menit sebesar 128,77 MPa, dan sampel tanpa perlakuan sebesar 94,63 MPa. Nilai kekerasan magnesium AZ31 menurun pada holding time 7 menit sebesar 39 VHN, bila dibandingkan sampel tanpa perlakuan sebesar 41,8 VHN.  Dan nilai kekerasan meningkat pada holding time 9 menit sebesar 46,2 VHN. Namun, perlu diperhatikan pemanasan dan holding time yang berlebih ( over heat ) dapat mengakibatkan penurunan sifat mekanik magnesium AZ31.